PENGARUH MOTIVASI INTRINSIK TERHADAP KEPUASAN KERJA PADA PT SOLUSINDO MITRA SEJAHTERA DI JAKARTA - Natassya Adinda Ayu Putri R. Ayu Putri R.; Yohanes Arianto Budi N. (Prosiding Working Papers Series In Management, 2018)
This study was conducted to determine the effect of intrinsic motivation on job satisfaction at cleaning service employee PT Solusindo Mitra Sejahtera, Jakarta. Independent variables in this research are achievement, recognition, work itself, responsibility, and progress, while the dependent variable in this research is job satisfaction. This research distributed questionnaires to 77 respondents from 95 populations. The results showed that the achievement, recognition, work itself, responsibility and progress of intrinsic motivation have a positive and significant effect on job satisfaction. Keywords: achievement, recognation, work itself, responsibility, advancement, job satisfaction.